Kloning Gen cry dari Bacillus turingiensis var. kurstaki - Nur Rahmi Ardiani; Sismindari Sismindari; Sudjadi Sudjadi (Universitas Gadjah Mada, 1998)
Bacillus thuringiensis is an entomopathogenic organism. The pathogenic effect is caused by crystalline protein, δ-endotoxin, which is encoded by the cry gene. The aim of this study was to clone the cry gene from B. thuringiensis var. kurstaki with a genomic library approach. HindIII digested B. thuringiensis total DNA was ligated to HindIII digested of pUC19, and then used to transform Escherichia coli DH5α. Selection of transformans carrying recombinant was done by α-complementation and a recombinant clone containing the cry gene was further screened by non-radioactive hybridization method using a probe synthesized from the conserved region of the published cry genes. The result suggested that two recombinant clones with the insert size of 3.4 kb and 2.0 kb, respectively, carrying the cry gene.